The Cultural Values in the Brokohan Tradition of the Javanese Community in Sonomartani Village, North Labuhanbatu Regency - Azhari, Sarah; Asari, Hasan (Yayasan Sembilan Pemuda Indonesia, 2025)
Brokohan tradition is a form of local wisdom inherited through generations among the Javanese community as an expression of gratitude for the birth of a child. Amid ongoing social dynamics, this tradition is still practiced by the Javanese people residing in Desa Sonomartani, North Labuhanbatu Regency. This study aims to analyze the cultural values contained in the brokohan practice and to describe its role in maintaining social cohesion and cultural identity among the diaspora community. Using a qualitative approach with ethnographic methods, the research explores the symbolic and social meanings of each element within the brokohan tradition. Data were collected through direct observation of the tradition’s implementation, interviews with traditional leaders, religious figures, and community members involved in the practice, as well as documentation in the form of photos and field notes. The findings reveal that brokohan is not merely a religious ritual but also embodies noble values reflecting the Javanese worldview, such as religiosity (devotion to God), mutual cooperation (selfless teamwork), kinship (a sense of belonging among residents), and cultural preservation (maintaining ethnic identity). Through brokohan, the community sustains social relations and strengthens communal solidarity. However, the study also finds that modernization and lifestyle changes have influenced the tradition’s execution in terms of form, timing, and meaning. Some community members have begun to replace traditional elements with modern ones, potentially eroding the original cultural values.